ANALISIS RISIKO GANGGUAN LAMBUNG PADA POLA MAKAN PEDAS DAN CARA PENANGANANNYA PADA GENERASI Z DI SATU WARALABA MIE PEDAS DI KOTA BEKASI - Simamora, Rotua Suriany; Sani, Aluwi Nirwana; Nurhayati, Nunung; Warti, Lia; Rahma, Icha Saeful; Setiadi, Feri (Jurnal Medicare, 2025)
Spicy food has now become a favorite among many young people, especially Generation Z. In addition to its tantalizing taste, spicy food is often featured in social media content in the form of challenges. This habit can increase the risk of gastric disorders if not accompanied by proper knowledge and management. This study aims to determine the influence of spicy food consumption patterns, knowledge levels, and handling practices on the incidence of gastric disorders among Generation Z at a spicy noodle franchise in Bekasi City. The method used was quantitative correlational with a cross-sectional approach, involving 100 respondents. The results of the multiple linear regression test showed a correlation coefficient (R) of 0.610 (strong category) and an R Square of 0.372 (moderate category). The chi-square test showed a p-value for eating patterns of 0.000 < 0.05, knowledge of 0.001 < 0.05, and management of 0.000 < 0.05, indicating that all variables had a significant effect on gastric disorders. Based on the results of the study, it can be concluded that spicy eating patterns, knowledge, and handling practices significantly influence gastric disorders among Generation Z.